(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
In this paper, we introduce a new integral transformation, say g-transformation and is defined as follows: Which consider generalized of most known integral transformations and also it can be find a new special integral transformations. We have studied the properties of this transformation. We have presented the general formula of g-transformation for the derivative of functions in higher orders. We also clarified the relationship between this transform and some known integral transformations such as the Laplace Transform [3], Carson transformation and Sunudu transformation [5]. We introduce new result of shifting theorem.